Comparison of agar gel immunodiffusion test, rapid slide agglutination test, microbiological culture and PCR for the diagnosis of canine brucellosis - Keid, Lara B.; Soares, Rodrigo M.; Vasconcellos, Silvio A.; Megid, Jane [UNESP]; Salgado, Vanessa R.; Richtzenhain, Leonardo J. (Elsevier B.V., 2009)
The performance of the rapid slide agglutination test, with and without 2-mercaptoethanol (RSAT and 2ME-RSAT) and agar gel immunodiffusion test (AGID) was evaluated for the diagnosis of brucellosis in naturally infected dogs. The microbiological culture, PCR and clinical parameters were used as reference. A total of 167 dogs were clinically examined and tested by blood culture, culture of semen/vaginal swab and PCR in blood and semen/vaginal swab. According to the results observed the 167 dogs were divided into three groups: Brucella canis infected dogs (Group 1). B. canis non-infected dogs (Group 2) and dogs with suspected brucellosis (Group 3). The dogs were then tested by RSAT, 2ME-RSAT and AGID. Groups 1 and 2 were used to calculate the diagnostic sensitivity and specificity of the serological tests and the results observed in Group 3 were also discussed. The diagnostic sensitivity of RSAT, 2ME-RSAT and AGID was respectively 70.58%, 31.76%, and 52.94%. The diagnostic specificity of RSAT, 2ME-RSAT and AGID was respectively 83.34%, 100%, and 100%. In dogs with suspected brucellosis 15% were RSAT positive, none was 2ME-RSAT positive and 5% were AGID positive. Although the serological tests are the most commonly used methods for brucellosis diagnosis, a significant proportion of false-negative results were observed highlighting the importance of the direct methods of diagnosis, like blood culture and PCR to improve the diagnosis of canine brucellosis. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Brucella canis; Canine brucellosis; Agar gel immunodiffusion test; Rapid slide agglutination test; PCR; Microbiological culture